ANALISIS PRODUK ASURANSI UNIT LINK DI INDONESIA - WIDANA, I NYOMAN; JAYANEGARA, KETUT (E-Jurnal Matematika, 2019)
This paper presents a unit-linked insurance  which is a modern insurance. The policyholders will get benefits of insurances and investment. The aim of this research is  to analysis of unit link insurance products in Indonesia. Especially to analysis the mortality cost, premium, return, and profit of the product.  The method used is a stochastic profit testing method and the results of the study show that mortality cost offered by the three unit link companies selected as the sample of this study are greater than the insurance costs calculated based on the Indonesian Mortality Table. From comparing different unit linked insurance plans, only one plan is sufficient to fund the guarantee. While others have to do a Top-up premium.